2017
DOI: 10.1016/j.omtn.2017.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for In Vivo Screening and Mitigation of Hepatotoxicity Associated with Antisense Drugs

Abstract: Antisense oligonucleotide (ASO) gapmers downregulate gene expression by inducing enzyme-dependent degradation of targeted RNA and represent a promising therapeutic platform for addressing previously undruggable genes. Unfortunately, their therapeutic application, particularly that of the more potent chemistries (e.g., locked-nucleic-acid-containing gapmers), has been hampered by their frequent hepatoxicity, which could be driven by hybridization-mediated interactions. An early de-risking of this liability is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 26 publications
4
39
0
1
Order By: Relevance
“…(18) Also, DGAT2 was inhibited by using ASO treatment, which may have off-target effects, such as decreasing DGAT2 expression in the adipose (16) or causing hepatotoxicity independent of the intended target. (19) In our study, the findings of similar degrees of inflammation and fibrosis between genotypes with different hepatic TG content suggests that the amount of hepatic TG is not solely responsible for disease progression. A limitation of interpreting the NASH endpoints in our study is that we found only modest development of fibrosis over several weeks.…”
Section: Female Control Female Ldgat2kosupporting
confidence: 48%
See 2 more Smart Citations
“…(18) Also, DGAT2 was inhibited by using ASO treatment, which may have off-target effects, such as decreasing DGAT2 expression in the adipose (16) or causing hepatotoxicity independent of the intended target. (19) In our study, the findings of similar degrees of inflammation and fibrosis between genotypes with different hepatic TG content suggests that the amount of hepatic TG is not solely responsible for disease progression. A limitation of interpreting the NASH endpoints in our study is that we found only modest development of fibrosis over several weeks.…”
Section: Female Control Female Ldgat2kosupporting
confidence: 48%
“…However, the latter study utilized a nutrient‐deficient diet to induce hepatic inflammation and fibrosis, which does not mimic other features of MetS, and, in fact, mice on the MCD diet lose weight . Also, DGAT2 was inhibited by using ASO treatment, which may have off‐target effects, such as decreasing DGAT2 expression in the adipose or causing hepatotoxicity independent of the intended target . In our study, the findings of similar degrees of inflammation and fibrosis between genotypes with different hepatic TG content suggests that the amount of hepatic TG is not solely responsible for disease progression.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“… 1 , 2 Despite these advantages, ASOs with high-affinity modifications have been associated with a higher risk of inducing liver toxicity. 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 Recent in vivo data suggest that the observed hepatotoxicity is hybridization dependent and requires RNase H1 activity. 10 , 12 Furthermore, the affinity of an ASO is considered to be associated with its hepatotoxic potential, likely because high-affinity ASOs can bind to and mediate cleavage of more unintended target RNAs than lower affinity ASOs.…”
Section: Introductionmentioning
confidence: 99%
“…One proposed mechanism of hepatotoxicity for some high-affinity ASOs is reduction of a high number of unintended transcripts due to RNase H1-dependent RNA degradation [8,12,60]. The 96 ASOs in this study resulted from extensive screening of ASOs and showed no hepatotoxicity or immune stimulation in standard rodent toxicology studies.…”
Section: Aso_059mentioning
confidence: 94%